2011
DOI: 10.1111/j.1469-1809.2011.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Penetrance of Hereditary Atypical Hemolytic Uremic Syndrome

Abstract: SummaryHereditary atypical hemolytic uremic syndrome (aHUS), a dramatic disease frequently leading to dialysis, is associated with germline mutations of the CFH, CD46, or CFI genes. After identification of the mutation in an affected aHUS patient, single-site gene testing of relatives is the preventive care perspective. However, clinical data for family counselling are scarce.From the German-Speaking-Countries-aHUS-Registry, 33 index patients with mutations were approached for permission to offer relatives scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Between 2000 and 2008, the mean number of patients referred each year at the time of the first episode of aHUS was 15 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21], suggesting that the annual incidence of aHUS is at least 0.23/year per 10 6 people in the French population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2000 and 2008, the mean number of patients referred each year at the time of the first episode of aHUS was 15 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21], suggesting that the annual incidence of aHUS is at least 0.23/year per 10 6 people in the French population.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic screening of patients with aHUS from national or international registries has provided an estimation of the frequency of mutations in the complement genes (9)(10)(11)(12). In contrast, our knowledge of the presentation and outcome of aHUS derives from only a few series (9,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Sullivan et al studied affected individuals and their relatives. The penetrance in 18 affected index cases with a CFH mutation was 67% by the age of 40 years and 100% by the age of 65 years 25. Two of the index cases had a further family member who was affected by the disease and both were found to carry the same CFH mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the penetrance of aHUS in carriers of complement gene mutations is incomplete, 1,2,4,5,7,27,33,34 and some subjects never develop aHUS or manifest the disease very late in adulthood. An epidemiologic study in familial cases reported that penetrance of aHUS by age 45 years was 50% among carriers of gene mutations.…”
Section: Discussionmentioning
confidence: 99%